Imaging Challenge in Recurrent Spontaneous Coronary Artery Dissection (SCAD): A Case Report - Martino, Giovanni; Leporace, Mario; Greco, Francesco; Quarta, Rossella; Romano, Letizia; Curcio, Antonio; Polimeni, Alberto (Journal of Cardiology and Cardiovascular Medicine, 2024)
Spontaneous Coronary Artery Dissection (SCAD) represents a significant cause of acute coronary syndrome (ACS) in patient populations with low-risk cardiovascular profiles and, therefore can be sometimes underdiagnosed. On the other hand, it often preserves the typical clinical presentation of ACS which makes coronary artery angiography (CAG) execution mandatory. A 62-year-old woman with a history of recurrent SCAD presented to the emergency department for a new episode of acute chest pain with troponin elevation. CAG revealed an ambiguous angiography image suggesting a sub-occlusive type 2 SCAD involving the distal segment of the left circumflex artery. The patient was managed conservatively due to the absence of ongoing ischemia or hemodynamic instability. At the seven-day follow-up, a computed tomography coronary angiography (CTCA) was performed to better assess SCAD and detect concomitant associated arteriopathies. Optimized medical therapy was prescribed at the discharge and at one-month follow-up, no recurrence of symptoms was referred.